Regulatory T Cells Accumulate in the Lung Allergic Inflammation and Efficiently Suppress T-Cell Proliferation but Not Th2 Cytokine Production. (15th November 2011) - Faustino, Lucas; Mucida, Daniel; Keller, Alexandre Castro; Demengeot, Jocelyne; Bortoluci, Karina; Sardinha, Luiz Roberto; Carla Takenaka, Maisa; Basso, Alexandre Salgado; Faria, Ana Maria Caetano; Russo, Momtchilo
Abstract : Foxp3 + CD25 + CD4 + regulatory T cells are vital for peripheral tolerance and control of tissue inflammation. In this study, we characterized the phenotype and monitored the migration and activity of regulatory T cells present in the airways of allergic or tolerant mice after allergen challenge. To induce lung allergic inflammation, mice were sensitized twice with ovalbumin/aluminum hydroxide gel and challenged twice with intranasal ovalbumin. Tolerance was induced by oral administration of ovalbumin for 5 consecutive days prior to OVA sensitization and challenge. We detected regulatory T cells (Foxp3 + CD25 + CD4 + T cells) in the airways of allergic and tolerant mice; however, the number of regulatory T cells was more than 40-fold higher in allergic mice than in tolerant mice. Lung regulatory T cells expressed an effector/memory phenotype (CCR4 high CD62L low CD44 high CD54 high CD69 + ) that distinguished them from naive regulatory T cells (CCR4 int CD62L high CD44 int CD54 int CD69 − ). These regulatory T cells efficiently suppressed pulmonary T-cell proliferation but not Th2 cytokine production.